2014
DOI: 10.1104/pp.114.243642
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evidence for the Critical Amino-Terminal Conserved Domain and Key Amino Acids of Arabidopsis 4-HYDROXY-3-METHYLBUT-2-ENYL DIPHOSPHATE REDUCTASE    

Abstract: The plant 4-HYDROXY-3-METHYLBUT-2-ENYL DIPHOSPHATE REDUCTASE (HDR) catalyzes the last step of the methylerythritol phosphate pathway to synthesize isopentenyl diphosphate and its allyl isomer dimethylallyl diphosphate, which are common precursors for the synthesis of plastid isoprenoids. The Arabidopsis (Arabidopsis thaliana) genomic HDR transgene-induced gene-silencing lines are albino, variegated, or pale green, confirming that HDR is essential for plants. We used Escherichia coli isoprenoid synthesis H (Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…21 Unexpectedly, the IspH domain of the Arabidopsis HDR corresponding to the full-length IspH of E. coli failed to complement the E. coli ispH mutant. 21 Nonetheless, several key amino acids involved in iron-sulfur formation, substrate binding or catalytic reaction in E. coli IspH were conserved in Arabidopsis HDR. Homology modeling and substrate docking of the IspH domain of the Arabidopsis HDR revealed that these key residues were also located in the central active site.…”
Section: -29mentioning
confidence: 99%
See 4 more Smart Citations
“…21 Unexpectedly, the IspH domain of the Arabidopsis HDR corresponding to the full-length IspH of E. coli failed to complement the E. coli ispH mutant. 21 Nonetheless, several key amino acids involved in iron-sulfur formation, substrate binding or catalytic reaction in E. coli IspH were conserved in Arabidopsis HDR. Homology modeling and substrate docking of the IspH domain of the Arabidopsis HDR revealed that these key residues were also located in the central active site.…”
Section: -29mentioning
confidence: 99%
“…Homology modeling and substrate docking of the IspH domain of the Arabidopsis HDR revealed that these key residues were also located in the central active site. 21 In addition to the conserved key amino acids, the Arabidopsis HDR contains several critical residues that are absent in the bacterial enzyme. 21 These results implicate that the reaction mechanism of plant HDR may be different from that of E. coli IspH.…”
Section: -29mentioning
confidence: 99%
See 3 more Smart Citations